2016
DOI: 10.1080/19425120.2016.1227889
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Use of Shallow and Deepwater Habitats by Juvenile Pacific Salmon in the Columbia River Estuary Prior to Ocean Entry

Abstract: The degree to which fine‐scale habitat use by salmonid species and stocks varies within habitat types such as estuaries is not fully resolved. We sampled shallow shoreline and deeper main‐stem channel habitats in the Columbia River estuary over 3 years to compare salmon species composition, migration timing, density, size, and production type (hatchery or natural). Results indicated a high degree of spatial heterogeneity in habitat occupancy by the five salmonid species that are native to the basin. Salmonid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
(86 reference statements)
0
14
0
Order By: Relevance
“…Juvenile salmon are known to distribute according to geospatial factors such as proximity to land (Bottom, Jones, Cornwell, Gray, & Simenstad, ; Roegner et al, ) and freshwater outflow (J. S. Macdonald et al, ). In this study, distance from the river mouth was not an important factor in describing the spatial distribution of juvenile salmon in the Skeena River estuary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Juvenile salmon are known to distribute according to geospatial factors such as proximity to land (Bottom, Jones, Cornwell, Gray, & Simenstad, ; Roegner et al, ) and freshwater outflow (J. S. Macdonald et al, ). In this study, distance from the river mouth was not an important factor in describing the spatial distribution of juvenile salmon in the Skeena River estuary.…”
Section: Discussionmentioning
confidence: 99%
“…Because much of the habitat closer to shore (within <5 m) is subtidal and can be sampled with the 9 m or 5 m deep purse seines, an association with locations closer to shore suggests that fish were found in higher abundances in subtidal nearshore habitat on channel margins compared with open water between landforms. In other estuaries, larger sub‐yearlings and yearling Chinook and coho salmon are associated with deeper channel or channel margin habitats (10–15 m deep; (Gamble et al, ; Pinnix, Nelson, Stutzer, & Wright, ; Roegner et al, ), whereas smaller fry or sub‐yearling Chinook are associated with shallow nearshore habitat (<3 m deep; Bottom, Jones, et al, ; Hering et al, ; Roegner et al, ; Simenstad et al, ). As both, coho (73–242 mm) and Chinook (85–185 mm) salmon found in the Skeena River estuary are primarily larger age classes (subyearling or ≥1 age class—using designations from Roegner et al, and Weitkamp et al, ), results from this study are comparable to findings from other estuaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But all estuary habitat is not the same for all salmonids: the five species of Pacific salmon present in the Columbia River estuary use shallow or deep estuary habitats at different times of the year in different ways (Roegner et al. ).…”
Section: Habitat Connectivity In Different Environmentsmentioning
confidence: 99%
“…Lowerestuary purse-seine surveys found that over 90% of the Chinook and Coho salmon and steelhead in deepwater habitats originate from hatcheries (Weitkamp et al 2012). Hatchery fish also have been collected in some shallow nearshore areas (Roegner et al 2012(Roegner et al , 2016Sather et al 2016), but the combined effects of all hatchery releases on the densities, stock composition, and size characteristics of salmon in these habitats are poorly understood. It is unknown, for example, whether large size at release effectively segregates HO smolts from NP juveniles in most shallow estuarine nursery areas or whether significant overlap enables hatchery fish to dominate or displace smaller NP juveniles (e.g., Nickelson et al 1986).…”
mentioning
confidence: 99%